Jelly belly protein activates the receptor tyrosine kinase Alk to specify visceral muscle pioneers. - Lee, H.H.; Norris, A.; Weiss, J.D.; Frasch, M. (Nature, 2003)
The secreted protein Jelly belly (Jeb) is required for an essential signalling event in Drosophila muscle development. In the absence of functional Jeb, visceral muscle precursors are normally specified but fail to migrate and differentiate. The structure and distribution of Jeb protein implies that Jeb functions as a signal to organize the development of visceral muscles. Here we show that the Jeb receptor is the Drosophila homologue of anaplastic lymphoma kinase (Alk), a receptor tyrosine kinase of the insulin receptor superfamily. Human ALK was originally identified as a proto-oncogene, but its normal function in mammals is not known. In Drosophila, localized Jeb activates Alk and the downstream Ras/mitogen-activated protein kinase cascade to specify a select group of visceral muscle precursors as muscle-patterning pioneers. Jeb/Alk signalling induces the myoblast fusion gene dumbfounded (duf; also known as kirre) as well as org-1, a Drosophila homologue of mammalian TBX1, in these cells.